Impacts of ecotourism development in Tasik Kenyir on the quality of life as perceived by the local community - Mohd Adam, Syamimi; Shuib, Ahmad; Ramachandran, Sridar; Kunasekaran, Puvaneswaran (Penerbit Universiti Malaysia Terengganu, 2019)
This study attempts to investigate how impacts of ecotourism development influence the quality of life, as perceived by the communities. In this study the local community chosen consists of members of three selected villages, within the proximity of Tasik Kenyir ecotourism centre. Data has been collected using questionnaires, during face-to-face interviews with 260 heads of household in the three villages identified. A descriptive analysis shows that, in general, the community agrees with the impacts of the ecotourism development in the area. Multiple regression procedures have been conducted to determine the causal relationships. The findings of the study indicate that four ecotourism impact factors have influenced the communities’ perception on the quality of life and these include household income, location of residence from ecotourism site, number of family members participating in ecotourism development, and perceived environmental impacts. This study is important for local authorities to identify possible economic options for local communities and to provide skill training programmes that are related to the tourism industry, to further enhance the quality of life.